1984
DOI: 10.1037/h0099630
|View full text |Cite
|
Sign up to set email alerts
|

How professionals can share power with families: Practical approaches to working with families of the mentally ill.

Abstract: A large percentage of the severely mentally ill in the community live with family members. Families look toward professionals as a major resource in assisting their disabled family members. Unfortunately, their relationships with professionals have often left families feeling blamed, discounted, and frustrated. The authors present a number of suggestions for what professionals can do to work more cooperatively with families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
4

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 8 publications
(13 reference statements)
1
34
0
4
Order By: Relevance
“…Collins and Collins (1990) concluded that many parent self-help groups and consumer's groups such as National Alliance for the Mentally Ill (NAMI) have formed because of parents' perception of a lack of power over their children's treatment. Although no speci c research was found that addressed the impact of blaming on parent involvement during their child's hospitalization , related research and expert opinion suggest this as a possible factor (Baker, Heller, Blacher, & Pfeiffer, 1995;Biegel, Song, & Milligan, 1995;Spaniol, Zipple, & Fitzgerald, 1994;Tessler, Gamache, & Fisher, 1991). The belief that parents are responsible for their children's disturbances has in uenced the nursing care of children on child psychiatric units, the parents' involvement, and the staff's responses to parents for many years and may still be a factor in parents' decision to manage the hospitalizatio n by having minimal contact with the staff.…”
mentioning
confidence: 97%
“…Collins and Collins (1990) concluded that many parent self-help groups and consumer's groups such as National Alliance for the Mentally Ill (NAMI) have formed because of parents' perception of a lack of power over their children's treatment. Although no speci c research was found that addressed the impact of blaming on parent involvement during their child's hospitalization , related research and expert opinion suggest this as a possible factor (Baker, Heller, Blacher, & Pfeiffer, 1995;Biegel, Song, & Milligan, 1995;Spaniol, Zipple, & Fitzgerald, 1994;Tessler, Gamache, & Fisher, 1991). The belief that parents are responsible for their children's disturbances has in uenced the nursing care of children on child psychiatric units, the parents' involvement, and the staff's responses to parents for many years and may still be a factor in parents' decision to manage the hospitalizatio n by having minimal contact with the staff.…”
mentioning
confidence: 97%
“…although Gottlieb (1985) has argued in favour of assessing (Spaniol et al 1984, Lefley 1988, Bawden 1990, Baker & Douglas 1990, Burns et al 1991. This trend is acknowl-the role of social support in coping with stress.…”
mentioning
confidence: 99%
“…C'est dans ce contexte que des chercheurs et chercheures ont mis en relief le fardeau que représentent, pour les parents, les difficultés d'interaction avec le système de soins et l'inadéquation des ressources communautaires par rapport à leurs besoins (Carpentier et al, 1992;Francell et al, 1988;Gubman et Tessler, 1987;Holden et Lewine, 1982;Lefley, 1987bLefley, , 1989McElroy, 1987aMcElroy, , 1987bSpaniol et al, 1984). Ceux et celles qui se sont intéressés à connaître ce que les familles attendaient du système de soins par rapport aux troubles de leur parent ont fait ressortir de façon cohérente qu'elles désiraient: 1) dès le début de l'apparition des troubles, de l'information en ce qui a trait aux symptômes, au traitement (principalement l'administration de la médi-cation et ses effets secondaires) et au pronostic; 2) des conseils pratiques sur la gestion des épisodes psychotiques et sur la vie quotidienne avec leur parent, lors de visites à domicile ou autrement; 3) une continuité dans le soin offert; et 4) le développement de ressources communautaires (Bernheim et Switalski, 1988;Gregory, 1989;Guberman et al, 1991;Hatfield, 1979aHatfield, , 1979bHatfield, , 1987aMacCarthy et al, 1989;StOnge et Lavoie, 1987;Tessler et al, 1991;Zirul et al, 1989).…”
Section: Les Soins Professionnels Et Les Personnes-soutiensunclassified